Immune mechanisms associated with cardiovascular disease in systemic lupus erythematosus: A path to potential biomarkers - Guzmán-Martínez, Gabriela; Marañón, Concepción; , CYTED RIBLES Network; Blasini, Ana María; González-Rumayor, Víctor; Muñoz-Louis, Roberto; Pons-Estel, Bernardo A.; Pons-Estel, Guillermo; Quintana, Rosana; Rodríguez, Martín A.; Ugarte-Gil, Manuel F.; Vásquez, Gloria (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) patients display an increased risk of cardiovascular disease (CVD). With the improved clinical management of other classical severe manifestation of the disease, CVD is becoming one of the most relevant complications of SLE, and it is an important factor causing morbidity and mortality. Several immune constituents have been shown to be involved in the pathogenesis of atherosclerosis and endothelial damage in SLE patients, including specific circulating cell populations, autoantibodies, and inflammatory mediators. In this review, we summarize the presentation of CVD in SLE and the role of the autoimmune responses present in SLE patients in the induction of atherogenesis, endothelial impairment and cardiac disease. Additionally, we discuss the utility of these immune mediators as early CVD biomarkers and targets for clinical intervention in SLE patients.